Legal Challenges in Criminal Execution of The Environmental Crime Cases in Indonesia: Efforts Toward Criminal Law Reform - Widyawati, Anis; Fernando, Zico Junius; Arifin, Ridwan; Mursyid, Ali Masyhar (Faculty of Law, Jambi University, 2026)
Environmental crimes in Indonesia, including illegal logging, pollution, and ecosystem destruction, continue to pose serious challenges despite the existence of an extensive regulatory framework. Most previous studies on environmental law enforcement in Indonesia have focused on investigation, evidentiary issues, or corporate criminal liability, while the execution of criminal judgments in environmental cases remains underexamined. This article analyzes the legal and institutional obstacles affecting the execution of criminal judgments in environmental crime cases, particularly those involving corporations, fines, additional sanctions, and environmental restoration orders. This study employs normative legal research using statutory, conceptual, and comparative approaches. It examines Law on Environmental Protection and Management, the Criminal Code, the Criminal Procedure Code, and relevant sectoral regulations, and compares the Indonesian framework with selected practices in Germany, Brazil, and the United States. The analysis demonstrates that regulatory disharmony, overlapping institutional authority, limited procedural clarity, and weak post-judgment enforcement mechanisms undermine the effectiveness of environmental criminal law enforcement. The article argues that the central weakness of Indonesian environmental criminal enforcement lies in the post-judgment stage, where fines, additional penalties, corporate compliance orders, and restoration measures frequently remain ineffective in practice